The Influence of Organizational Culture, Employee Engagement, Organizational Communication, and Self-Efficacy on Employee Performance with Knowledge Sharing as a Mediating Variable - Nanda Cantika Malaysiene; Tri Handayani (Business, Accounting, and Knowledge Journal, 2025)
This study aims to analyze the influence of organizational culture, employee engagement, organizational communication, and self-efficacy on employee performance with knowledge sharing as a mediating variable among Generation Z employees at PT. Casuarina Harnessindo Pemalang. The research method used in this study employs a quantitative approach. The population in this study consists of 1,818 Generation Z employees at PT. Casuarina Harnessindo Pemalang in September 2024. Based on the Slovin formula, the sample used in this study consisted of 100 respondents. The sampling technique used in this study is purposive sampling. The data analysis technique used in this research is multiple linear regression analysis. Through this research, the researcher conducted data processing in 2 equations, where knowledge sharing and employee performance are the dependent variables. The results of this study indicate that the variables of organizational culture, employee engagement, organizational communication, self-efficacy, and knowledge sharing have a positive and significant impact on employee performance, and the variable knowledge sharing is able to mediate the influence of organizational culture, employee engagement, organizational communication, and self-efficacy on the employee performance of Generation Z at PT. Casuarina Harnessindo Pemalang. These findings highlight the importance of organizational culture, employee engagement, organizational communication, self-efficacy, and knowledge sharing in improving employee performance, particularly for Generation Z employees at PT. Casuarina Harnessindo Pemalang.